Assessment On Losses Due To The 2080/2023 Earthquake In Jajarkot District, Nepal - Bista, Amar Bahadur; Dahal, Khetraj; Gyawali, Prakash (International Journal on Engineering Technology, 2026)
Nepal, positioned along the tectonically active Himalayan zone, is particularly prone to earthquakes. The Jajarkot earthquake of November 3, 2023 (Mw 5.7, ML 6.4) caused significant loss of life and property in Chhedagad Municipality of Jajarkot District. This study aimed to assess the losses and their underlying causes in the aftermath of this earthquake.  Data were collected through Primary and Secondary method. Quantitative data were analyzed using Microsoft Excel with Relative Importance Index (RII) applied to Likert-scale items. Results indicated that the most significant losses included damages to public infrastructure with RII = 0.80. The dominant causes was structural vulnerabilities of traditional stone-wall construction (RII = 0.80. Recommended mitigation measures include accurate mortality assessment, integrated planning with resilient infrastructure design, and multi-agency collaboration among local governments, NGOs, and international bodies. This study provides a critical evidence base for disaster risk reduction policy and practice in seismically active remote regions of Nepal.